PENGARUH TINGKAT PENDIDIKAN TERHADAP JUMLAH PENDUDUK MISKIN PROVINSI JAWA TIMUR MENGGUNAKAN REGRESI SPASIAL - Sri Wahyuni; Hery Tri Sutanto (Universitas Negeri Surabaya, 2020)
The number of poorness in East Java was influencing to economics growth and people prosperities. Spatial regression is analyzing of regression model to identification factors that comes with location. Djuraidah and Wigena (2012) says that factor of poorness for SAR model are inversed to poorness percentage. In this paper will talk about factors that is influencing East Java poorness using level of education. Where the level od education is composed by elementary school (X1), middle school (X2), high school (X3), and vocational school (X4). Using Queen Continguity dan software R, we will analyze spatial regression using SAR and SEM model to get best model. And we will know that SAR model for poorness of East Java is: And SEM model for poorness of East Jawa is : where X3 and X4 are the influencer to East Java poorness. Keywords: Spatial regression, SAR, SEM, Queen Continguity